解方程(组): (1)4(2-x)2-9=0; (2)x2-2
(3)(x-1)2-5(x-1)+6=0; (4)
(5)
|
(1)4(2-x)2-9=0
变形得:(2-x)2=9 4
解得:x1=
,x2=7 2
;1 2
(2)x2-2
x+1=05
a=1,b=-2
,c=15
b2-4ac=(-2
)2-4×1×1=16,5
x=
=-(-2
)±5 16 2×1
±25
x1=
+2,x2=5
-2;5
(3)(x-1)2-5(x-1)+6=0
因式分解得,(x-1-2)(x-1-3)=0
解得:x1=3,x2=4;
(4)
-x+1 x2
=12x2 x+1
设
=m①x+1 x2
则原方程变为:m2-m-2=0
解得:m1=-1,m2=2;
把m的值代入①式解得x1=1,x2=-1 2
经检验,x1=1,x2=-
是原方程的解,1 2
所以原方程的解为x1=1,x2=-
;1 2
(5)
.x+y=14 xy=24
由x+y=14,得x=14-y①
将①式代入xy=24,得(14-y)y=24,
解得:y=12或y=2,
所以x=2或12,
所以原方程组的解为:
;x1=2 y1=12
;x2=12 y2=2